Desenvolvimento do estudo de funções exponenciais e logarítmicas e suas aplicações interdisciplinares - FARIAS, João Paulo de Azevedo (2023)
Mathematics has gone through various cycles of transformations, which will provide us with a better understanding, methods and applications of modern science. And these transformations are directly linked to the need of man to understand phenomena, situations and the proper coexistence of man-nature relationships. Being thus, the development of two logarithms and exponentials, or better, of the logarithmic and exponential functions, would have a fundamental role for this development, in view of the fact that, for the same two centuries past, carry out operations of multiplication, division, power and radiation, It was an arduous task, which without using computer tools as we know it today, would take years to carry out a job like this, BOYER; MERZBACH, (2012), in his work on planetary orbits, with not so conventional methodologies. In relation to methodology, it is of a theoretical nature, I have in view a detailed formalism on properties, mathematical formulations and graphs of exponential and logarithmic functions and based on contextualization and interdisciplinary with problems faced in the daily life of the student. In this way, this article emphasizes the development of the study of exponential and logarithmic functions and their interdisciplinary applications, considering that it is relevant for a better understanding of the theory as well as adding to a brief historical account of the development of the concepts of exponential and logarithmics in relation to the way we know it today. , highlighting some two great mathematicians who contributed to the topic addressed. As for the applications of the functions, we insert some contextualized problems (ENEM, years 2012, 2016 and 2017) related to everyday life. The research was concluded considering that the approach carried out on the two aspects of theory and practice, can be carried out and applied in the context of the classroom and that they can contribute to a better teaching and learning process, once the student begins to understand the field of application with problems linked to his daily life.